2021
DOI: 10.1097/cce.0000000000000505
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Future Care Requirements Using Machine Learning for Pediatric Intensive and Routine Care Inpatients

Abstract: Develop and compare separate prediction models for ICU and non-ICU care for hospitalized children in four future time periods (6-12, 12-18, 18-24, and 24-30 hr) and assess these models in an independent cohort and simulated children's hospital. DESIGN:Predictive modeling used cohorts from the Health Facts database (Cerner Corporation, Kansas City, MO). SETTING:Children hospitalized in ICUs. PATIENTS:Children with greater than or equal to one ICU admission (n = 20,014) and randomly selected routine care child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…This study demonstrated the applicability of the CI-M for assessments of serial changes in mortality risk for individuals. The Criticality Index was initially calibrated to probability of ICU care and has been applied to determining future care needs for hospitalized children (7). This study expands its use by recalibrating it to mortality risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study demonstrated the applicability of the CI-M for assessments of serial changes in mortality risk for individuals. The Criticality Index was initially calibrated to probability of ICU care and has been applied to determining future care needs for hospitalized children (7). This study expands its use by recalibrating it to mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…We computed each admission's Criticality Index for each time period using the previously published machine learning methodology and detailed in Supplemental Digital Data 1 (http://links.lww.com/ PCC/B978) (5)(6)(7). Previously, we demonstrated that as the Criticality Index increases, the intensity and complexity of care increases.…”
Section: Machine Learning Methodology and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Vital signs, laboratory data, and medication data were standardized to values from 0 to 1 using the maximum and minimum values of the training set. Consistent with other machine learning models, the data for each time period were forward imputed using the last available data if new data were not obtained ( 16 , 17 , 20 23 ) For the first time period, if vital signs or laboratory data were not obtained, we used the medians of the first time periods across all training patients adjusted by 9 age groups. The imputed values by age groups are reported in Supplementary Appendix S4 .…”
Section: Methodsmentioning
confidence: 99%